2020
DOI: 10.21203/rs.2.22205/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pollen germination and hand pollination in pitaya (Hylocereus undatus)

Abstract: Hand pollination is a necessary aiding method for pitaya ( Hylocereus undatus ) production to achieve a high yield. With the cultivated area of pitaya going up exponentially in the recent years, a systematic study was carried out to understand the mechanism behind the high yield. In this study, we first developed an optimal medium for the in vitro germination of pitaya pollen. Upon testing the activity of the pollen collected from or stored for different time, we observed that the relative high pollen germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The presence of a high number of natural pollinators such as honey bees in the field plays a major role in fruit set in pitahaya fruits [27]. Total soluble solids, being the most desirable characteristic for consumer preference, is measured as Brix, which can be affected by a set of factors, such as genetic, climatic, soil, and management, among others [6].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a high number of natural pollinators such as honey bees in the field plays a major role in fruit set in pitahaya fruits [27]. Total soluble solids, being the most desirable characteristic for consumer preference, is measured as Brix, which can be affected by a set of factors, such as genetic, climatic, soil, and management, among others [6].…”
Section: Discussionmentioning
confidence: 99%
“…These data are very close to the observations of Ramos [24], although carrying out this activity from phase II is not ruled out (Figure 4). On the other hand, Li et al [25] found that the greater pollen activity or greater viability does not mean a greater fruit size, since pollinating at 04:00, the fruit set percentage can reach up to 99.2 % but fruit size is significantly 10.5 % smaller.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to add that authors such as Li et al, [25] pointed out that, although the pollen is not yet mature in the Hylocereus pistil, it is possible to apply it to the stigma where it can mature, but an impact of reduction of pollen activity and fruiting percentage will be observed.…”
Section: Resultsmentioning
confidence: 99%